Peranan Self Optimism Terhadap Academic Burnout pada Peserta Didik SMA dalam Peralihan Pembelajaran Daring ke Pembelajaran Luring - Lamhot Rumapea; Rika Vira Zwagery; Rusdi Rusli (Universitas Batanghari Jambi, 2023)
The COVID-19 pandemic has hit Indonesia which has had an impact on changing the learning system for students. One of these impacts causes problems, namely academic burnout. Students who experience academic burnout will have an effect on learning motivation and result in a decrease in learning achievement. Academic burnout is influenced by several factors, one of which is self-optimism. This study aims to determine the role of self-optimism on academic burnout in high school students in Banjarmasin, South Kalimantan. The population in this study are students who are currently carrying out high school education in Banjarmasin with a sample of 243 selected by random sampling. This study uses two measuring tools, namely the academic burnout scale and the self-optimism scale. Data analysis using simple linear regression analysis through SPSS version 25 for windows. Based on the results of the regression analysis, it was found that the role of self-optimism on academic burnout with t count = -5,400 with a significant value of 0.000. The coefficient of determination shows the role of self-optimism on academic burnout by 10.8%, while 89.2% is influenced by other factors not included in this study.